Proceedings of the 16th and 17th annual Hampton University Graduate Studies (HUGS) summer school on quarks, hadrons, and nuclei : (World Scientific, 2004)
This volume contains lectures presented at the Sixteenth and Seventeenth Annual Hampton University Graduate Studies at the Continuous Electron Beam Accelerator Facility (HUGS at CEBAF) Summer Schools. The HUGS summer school brings pedagogical lectures to graduate students who are working on doctoral theses in nuclear physics. It has a balance of theory and experiment, and lecturers address topics of high current interest in strong interaction physics, particularly in electron scattering. Many HUGS lecturers lead major experimental efforts, and are internationally renowned for their contributions to the field.